Validation of the optimal site in the neck region for detecting swallowing sounds. (4th October 2016) - Pan, Q.; Maeda, N.; Manda, Y.; Kodama, N.; Minagi, S.
Summary: Recently, the swallowing sound has been used to detect swallowing events non‐invasively. A previous study, using an accelerometer, showed that the site over the lateral border of the trachea immediately inferior to the cricoid cartilage was the optimal site for detecting swallowing sounds. However, the optimal site for detection of the swallowing sound using a microphone remains undetermined. To validate the optimal site in the neck region for detecting swallowing sounds. Fourteen healthy subjects (mean age, 27·6 ± 2·2 years; seven male and seven female) participated in this study. Twenty condenser microphones were attached to 20 sites on the left neck surface to detect swallowing sounds. Participants were instructed to swallow five different stimuli three times as follows: Resting saliva, 1 and 5 mL of Japanese tea, and 1 and 5 mL of yoghurt. Mean relative peak intensity was used to indicate the magnitude of the swallowing sound. Sound spectrograms were used to illustrate differences in the properties of swallowing sounds. Mean relative peak intensity number was highest in sites at the inferior border of the mandible just above the sternocleidomastoid muscle (site 11) and sites over the lateral border of the trachea immediately inferior to the cricoid cartilage (site 8). Comparison of spectrograms showed a greater density distribution of higher frequency components at site 11 compared with site 8. These results indicate that the inferior border of the mandible just above the sternocleidomastoid muscle is the optimal site for the detection of swallowing sounds.